Heart rate variability and cold-induced vascular dilation after stimulation of two different areas of the ear: a prospective, single-blinded, randomized crossover study - Emmanuel Sagui; Damien Claverie; Wahiba Bidaut; Laurent Grelot (BMC, 2024)
Abstract Background Both noninvasive transauricular vagus nerve stimulation (taVNS) and traditional medical practice (TMP), such as auriculotherapy, use the auricle as a starting point for stimulation, but with two different conceptual frameworks: taVNS depends on vagal afferences to account for its effects, whereas TMP requires stimulation of the ear with high topographical accuracy regardless of the afferent nerves. The aim of this study was to measure heart rate variability (HRV) and cold water-induced vasodilation (CIVD) after puncturing two different ear points with the same afference but that should have opposite effects according to TMP. Methods Ten healthy subjects were investigated in this single-blinded crossover study over three sessions. In the first session, sympathetic activation was performed via cold water immersion of the right hand, with recordings taken from multiple fingers. HRV was assessed in the time domain (square root of the mean squared differences of NN intervals (RMSSD)) and frequency domain (low (LF) and high frequencies (HF)). In the second and third sessions, the same skin immersion test was performed, and mechanical stimulation was applied to the ear at two different points on the internal surface of the antitragus, one with alleged parasympathetic activity and the other with alleged sympathetic activity. The stimulation was done with semipermanent needles. Results Stimulation of the point with alleged parasympathetic activity immediately resulted in a significant decrease in RMSSD in 75% of the subjects and in LF in 50% of the subjects, while stimulation of the point with alleged sympathetic activity resulted in an increase in HF and RMSSD in 50% of the subjects. Stimulation of these points did not affect the CIVD reflex. The 20 min cold water immersion induced an immediate decrease in LF and the LF/HF ratio and an increase in HF. The skin temperature of the nonimmersed medius significantly decreased when the contralateral hand was immersed, from 34.4 °C to 31.8 °C. Conclusions Stimulation of two different ear points innervated by the same afferent nerves elicited different HRV responses, suggesting somatotopy and a vagal effect beyond vagal afferences. These results are not in accordance with the claims of TMP. Trial registration NCT04130893 (18/10/2019) clinicaltrials.com.